Designing education democratically through deliberative crowdsourcing: the case of the Finnish curriculum for basic education. Issue 6 (2nd November 2021) - Säily, Laura; Huttunen, Rauno; Heikkinen, Hannu L. T.; Kiilakoski, Tomi; Kujala, Tiina
ABSTRACT: In Finland, curriculum design is allegedly carried out through a deliberative process that involves various stakeholders, interest groups, experts and ordinary citizens. To facilitate participation in curriculum design, online crowdsourcing has been applied. The objective of this study is to explore to what extent the design process of the latest Finnish national curriculum for mathematics was open, democratic and deliberative. The theoretical framework of the study is the theory of democratic will-formation of the German philosopher Jürgen Habermas. The comments given on the early version of the core curriculum of mathematics were analysed using directed content analysis, in which the above theory was applied. In the empirical analysis, the comments on the core curriculum were divided into three categories based on the quantity and quality of the arguments: strong, medium and weak modifications. Based on this empirical analysis, it is argued that majority of modifications suggested by commenters did not play a significant role in the curriculum design. Thus, in terms of the theory of democratic will-formation, there are legitimate reasons to suspect that the process was not as democratic as it was intended to be. To conclude, limits and opportunities for deliberative democracy in curriculum design are reflected upon.